DAMPAK MULTIDIMENSIONAL PROGRAM MAKAN BERGIZI GRATIS TERHADAP KUALITAS PENDIDIKAN DAN EKONOMI LOKAL: STUDI LITERATUR JURNAL - Septiana, Azis; Sunardi, Didi; Sidki, Ahmad; Duryat, Masduki (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The Free Nutritious Meals (MBG) program is a strategic policy of the Indonesian government aimed at improving the quality of human resources by fulfilling the nutritional needs of vulnerable groups such as toddlers, breastfeeding mothers, and especially for students. This study aims to analyze the multidimensional impact of the MBG on the quality of education and the local economy through a literature review approach. The method used was a systematic literature review of relevant national and international articles. Data were collected from the databases Google Scholar, Scopus, and SINTA using keywords related to school feeding programs and nutrition and education. The results indicate that the MBG program has a positive impact on improving learning concentration, student attendance, and nutritional status. On the other hand, this program also has an economic impact in the form of opportunities for the UMKM and agricultural sectors. However, the MBG program creates new problems for school canteen operators. Furthermore, several challenges arise in its implementation, such as distribution issues, food security, and inequality in access between regions. This study confirms that the success of the MBG program depends heavily on transparent governance, cross-sector integration, and adaptation to the local context.